Body Condition Score And Its Relationship With Milk Fat Per Cent And Weekly Milk Yield In Frieswal Cows - Kumar, Kamlesh; Nanavati, S.; Joshi, S. K.; Yadav, D. V. S.; Singh , Nidhi (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was carried out for Body Condition Score and its relation with production performance i.e. weekly milk yield and milk fat per cent along with the effect of parities and stages of lactation on Body Condition Score, weekly milk yield and milk fat per cent. Results of the study showed significant effect of parity on Body Condition Score, fat per cent and weekly milk yield. A significant effect of stages of lactation was observed on Body Condition Score and fat per cent. The Body Condition Score was found significantly correlated with weekly milk yield.